Phalaris angusta (Gramineae) causing neurological disease in cattle in the State of Santa Catarina, Brazil Phalaris angusta (Gramineae) como causa de enfermidade neurológica em bovinos no Estado de Santa Catarina - Gava A.* (1999)
Two outbreaks of spontaneous poisoning in cattle by Phalaris angusta Nees ex Trin.("aveia louca", "aveia de sangue") are reported in cattle. The outbreaks occurred in the State of Santa Catarina, Brazil, during the winters of 1993 and 1996. In both outbreaks the animals were held in paddocks where P. angusta was a prevalent forage. Clinical signs in affected cattle included generalized tremors, alertness, hypermetria, ataxia and convulsions. Gross lesions were restricted to the brain and consisted of gray to greenish discoloration in the thalamus and mesencephalon. The disease was experimentally reproduced in cattle by administration of P. angusta.